Are clusters resilient? Evidence from Canadian textile industries - Kristian Behrens; Brahim Boualam; Julien Martin (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Département des sciences économiques, 2018)
We investigate whether plants inside and outside geographic clusters differ in their resilience to adverse economic shocks. To this end, we develop a bottom-up procedure to delimit clusters using Canadian geo-coded plant-level data. Focussing on the textile and clothing industries and exploiting the series of dramatic changes faced by that sector between 2001 and 2013, we find no evidence that plants in clusters are more resilient than plants outside clusters: they are neither less likely to die nor more likely to adapt by switching their main line of business. However, conditional on switching, plants in urbanized clusters are more likely to transition to services.
Keywords: 330